Traction mechanical characterization of porcine mitral valve annulus. (January 2023) - Silva-Verissimo, W.; El Louali, F.; Godio-Raboutet, Y.; Leblond, Lugdivine; Sourdon, Joevin; Rapacchi, S.; Evin, Morgane
Abstract: The Mitral Annulus (MA) is an anisotropic, fibrous, flexible and dynamical structure. While MA dynamics are well documented, its passive mechanical properties remain poorly investigated to complete the design of adequate prostheses. Mechanical properties in traction on four sections of the MA (aortic, left, posterior and right segments) were assessed using a traction test system with a 30 N load cell and pulling jaws for sample fixation. Samples were submitted to a 1.5 N pre-load, 10 pre-conditioning cycles. Three strain rates were tested (5 %/min, 7 %/min and 13 %/min), the first two up to 10 % strain and the last until rupture. High-resolution diffusion-MRI provided microstructural mapping of fractional anisotropy and mean diffusion within muscle and collagen fibres. Ten MA from porcine hearts were excised resulting in 40 tested samples, out of which 28 were frozen prior to testing. Freezing samples significantly increased Young Moduli for all strain rates. No significant differences were found between Young Moduli at different strain rates (fresh samples 2.4 ± 1.1 MPa, 3.8 ± 2.2 MPa and 3.1 ± 1.8 MPa for increasing strain rates in fresh samples), while significant differences were found when comparing aortic with posterior and posterior with lateral (p < 0.012). Aortic segments deformed the most (24.1 ± 9.4 %) while lateral segments endured the highest stress (>0.3 MPa), corresponding to higher collagen fraction (0.46) and fractional anisotropy. Passive machinal properties differed between aortic and lateral segments of the MA. The process of freezing samples altered their mechanical properties. Underlying microstructural differences could be linked to changes in strain response.